CONCEPÇÕES DE TRABALHO DE CAMPO E ENSINO DE GEOGRAFIA NAS LICENCIATURAS DO SUDESTE GOIANO - CARNEIRO, Vandervilson Alves (2009)
The working-field is one of the more teaching traditional recourses of geographic área to get knowledge. This way has been important so in University as scholar ambient of fundamental, secondary teachings. The present research gets to know the teacher and students conception about the teaching recourse working field from universities Goiás South-east in geography courses in superior levels. The data were collected by questionnaires with teachers and students in their study working ambient. The analysis of the results enabled to present the working field conception from teachers and students. The investigation more detailed through graphics evidenced that there are important conceptions about teaching way named working-field applied together with the disciplines in question. In the presence of several working-field alternatives, students and teachers from Universidade Estadual de Goiás Unidade Universitária de Pires do Rio chose the motivating model and teachers and students from Universidade Federal de Goiás Campus de Catalão chose training model. Independently as for kind field choose and/or working-field modality, teachers and students must have surely about this activity because it is very important to geographyc knowledge and is through it that pictures, places and municipal areas are discovered.